Pengaruh Ukuran Perusahaan, Umur Perusahaan, dan Profitabilitas Perusahaan terhadap Nilai Perusahaan - Egita Nur Fadila; Febritya Ayu Wahyuni; Fradana Yudistiya Aldiyansa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This study aims to analyze the effect of firm size, firm age, and profitability on firm value. The companies used in this research are all coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. In obtaining the research sample, a purposive sampling method was used, in which there were 9 coal subsector companies that met the criteria and were used as research samples. The analysis used for this research is SPSS version 26 with multiple linear regression analysis. The results of the analysis show that firm size and firm age have a significant effect on firm value, while profitability has no effect on firm value. The limitations in this study are the limited number of samples and the use of variables taken from financial data. From this research it can be seen that the company is included in the large companies that are of interest to investors, so that the company's value increases.